Towards the History of English Studies in Lithuanian - Grigaliūnienė, Jonė (Kalbotyra, 2008)
The paper is an attempt to give an overview of several periods in the development of English Studies in Lithuania from its establishment as an independent academic discipline in 1923 until now. [...]